Description of Factors for Low Use of IUD in Women of Reproductive Age at Bertha Inpatient Primary Clinic Medan Deli District 2023 - Lesna Bu'ulolo; Bernadetta Ambarita; Elvi Febria (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2023)
Intra Uterine Device (IUD) is a tool or object that is inserted into uterus which is very effective, reversible and long term, and can be used by all women of reproductive age. The choice of contraceptive method can be influenced by several factors are knowledge, age, education, and parity, husband's support, etc. Objective: The purpose of this study is to determine the low use of IUDs in women of childbearing age at Bertha Inpatient Primary Clinic 2023. Methods: This type of research is descriptive. The population of all women of childbearing age as many as 43 respondents. The sampling technique is accidental sampling. Data collection uses primary data with questionnaire. Data analysis using univariate for frequency distribution. Results: The results of 43 respondents have knowledge about IUD family planning are 69.8% poor category. Husband's support by positive category are 93%. In receiving family planning information are 95% in positive category. It can be concluded that the low use of IUDs is due to the knowledge factor of women of childbearing age, the majority of whom have low knowledge about IUD contraception at Bertha Inpatient Primary Clinic 2023.